KAJIAN PENDAPATAN USAHATANI KELAPA DENGAN DIVERSIFIKASI HORIZONTAL PADA GAPOKTAN PETANI JAYA DI DESA POIGAR 1 KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN - Delke Susanti Kawau; Caroline B.D. Pakasi; Mex L. Sondakh; Leonardus R. Rengkung (AGRI-SOSIOEKONOMI, 2015)
This study aims to determine the income of coconut farmers with horizontal diversification and cropping pattern which provide coconut production and greater revenue. The result showed that amount of the income of coconut farmers with horizontal diversification more than the income of coconut farmers in cultivated monoculture. Horizontal diversification of cropping patterns provides the biggest income is coconut-rice field.